2014
DOI: 10.1242/jeb.107870
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and physiological studies of bigheaded carps demonstrate that the epibranchial organ functions as a pharyngeal taste organ

Abstract: The epibranchial organ (EO) is an enigmatic tubular organ found in the pharyngeal cavity of many filter-feeding fishes. We investigated whether it might function as a taste organ that mediates aggregation and ingestion of planktonic food within the buccal cavity. The EO and associated structures of bighead and silver carps, two successful and invasive planktivorous fishes, were examined using histological and electrophysiological techniques. Both species possess finely structured gill rakers that extend direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
16
2
Order By: Relevance
“…This final involution at the posterior end of the EBO creates a final exit between the posterior median triangular fold (#5, Figure a) and the pharyngeal jaws (Figure c). Contrary to results (for both bighead and silver carp) published by Hansen, Ghosal, Caprio, Claus, and Sorensen () no taste buds were found inside the EBO. Particles aggregated within the EBO are deposited onto the pharyngeal jaws.…”
Section: Discussioncontrasting
confidence: 99%
“…This final involution at the posterior end of the EBO creates a final exit between the posterior median triangular fold (#5, Figure a) and the pharyngeal jaws (Figure c). Contrary to results (for both bighead and silver carp) published by Hansen, Ghosal, Caprio, Claus, and Sorensen () no taste buds were found inside the EBO. Particles aggregated within the EBO are deposited onto the pharyngeal jaws.…”
Section: Discussioncontrasting
confidence: 99%
“…The gill raker and pharyngeal apparatus of bighead and silver carp is a highly specialized system for filtering and funneling food particles into the pharynx (Hansen, Ghosal, Caprio, Claus, & Sorensen, 2014;Walleser, Howard, Sandheinrich, Gaikowski, & Amberg, 2014;Wilamovski, 1972). Up to 88% of early generation bighead hybrids have deformed gill rakers (Lamer et al, 2010;Marian et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The SCC distribution is variable from one vertebrate species to the other. In aquatic vertebrates, they are widely distributed on the skin, gills, nasopharynx, or oropharynx (hagfish—Braun, , ; Braun & Northcutt, ; lampreys—Baatrup & Døving, ; Fox et al, ; Whitear & Lane, ; chondrichthyes—Peach, ; Whitear & Moate, ; bony fish—Codina et al, ; Hansen et al, ; Kotrschal, ; Kotrschal et al, , , ; Kuciel et al, ; Peters et al, , ; Silver & Finger, ; see Whitear, for a review). In terrestrial vertebrates, on the other hand, SCCs seem restricted to specific anatomical locations (e.g., the airways) (amphibians—Osculati & Sbarbati, ; Whitear, ; but see also for putative skin SCCs Koyama et al, ; Nagai et al, ; reptiles—Hansen, ; mammals—Finger et al, ; Saunders et al, ; Sbarbati et al, , ; Sbarbati & Osculati, ; Tizzano et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is only with the work of Whitear on the skin of teleost fish that the innervation, and thus sensory nature, of these cells was demonstrated (Lane & Whitear, ; Whitear, , , ). Subsequently, studies have reported putative SCCs on the barbels and nasopharynx of hagfish (Braun, , ; Braun & Northcutt, ), on the skin surface of brook lampreys ( Lampetra planeri Bloch) and river lampreys ( Lampetra fluviatilis L.), including the oral, gill pore, dorsal fin and genital regions (Baatrup & Døving, ; Fox, Lane, & Whitear, ; Whitear & Lane, ), on the skin, gills, and oropharynx of chondrichthyes and bony fish (Codina et al, ; Hansen, Ghosal, Caprio, Claus, & Sorensen, ; Kotrschal, ; Kotrschal, Krautgartner, & Hansen, ; Kotrschal, Peters, & Atema, ; Kotrschal, Whitear, & Adam, ; Kuciel et al, ; Peach, ; Peters, Kotrschal, & Krautgartner, ; Peters, Van Steenderen, & Kotrschal, ; Silver & Finger, ; Whitear & Moate, ). Other studies have described SCCs on the skin and in the oral cavity of amphibians (Koyama, Nagai, Takeuchi, & Hillyard, ; Nagai, Koyama, Von Seckendorff Hoff, & Hillyard, ; Osculati & Sbarbati, ; Whitear, ), and in the airways of reptiles and mammals (Finger et al, ; Hansen, ; Saunders, Christensen, Finger, & Tizzano, ; Sbarbati, Crescimanno, Benati, & Osculati, ; Sbarbati, Crescimanno, Bernardi, & Osculati, ; Sbarbati & Osculati, ; Tizzano et al, ; Tizzano, Merigo, & Sbarbati, ).…”
Section: Introductionmentioning
confidence: 99%